2017
DOI: 10.1016/j.virol.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

A live-attenuated influenza vaccine for H3N2 canine influenza virus

Abstract: Canine influenza is a contagious respiratory disease in dogs caused by two subtypes (H3N2 and H3N8) of canine influenza virus (CIV). Currently, only inactivated influenza vaccines (IIVs) are available for the prevention of CIVs. Historically, live-attenuated influenza vaccines (LAIVs) have been shown to produce better immunogenicity and protection efficacy than IIVs. Here, we have engineered a CIV H3N2 LAIV by using the internal genes of a previously described CIV H3N8 LAIV as a master donor virus (MDV) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(84 citation statements)
references
References 59 publications
6
76
0
2
Order By: Relevance
“…1B). Both combinations of plasmids (WT and LAIV) resulted in similar Gaussia luciferase (Gluc) expression levels at 33°C; however, Gluc expression was significantly reduced at higher temperatures (37°C and 39°C) in cells transfected with the pH1N1 LAIV plasmids, consistent with previous results shown for other IAV LAIV strains (9)(10)(11). Importantly, Western blot analysis shows similar levels of NP expression at each temperature for WT-and LAIV-transfected cells (Fig.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…1B). Both combinations of plasmids (WT and LAIV) resulted in similar Gaussia luciferase (Gluc) expression levels at 33°C; however, Gluc expression was significantly reduced at higher temperatures (37°C and 39°C) in cells transfected with the pH1N1 LAIV plasmids, consistent with previous results shown for other IAV LAIV strains (9)(10)(11). Importantly, Western blot analysis shows similar levels of NP expression at each temperature for WT-and LAIV-transfected cells (Fig.…”
Section: Resultssupporting
confidence: 89%
“…First, because a recombinant pH1N1 harboring inhibitory PA-X and NS1 proteins could lead to a more virulent virus (35)(36)(37)(38), we selected, for safety reasons, to use the ca, ts, and att pH1N1 LAIV virus. Second, we and others have previously shown that LAIVs provide a more sensitive approach to study mutations affecting overall viral replication and pathogenicity (5,7,(9)(10)(11)39). Finally, the results obtained from our studies could be used to identify and develop more efficient LAIV candidates with acceptable safety profiles by modulating the virus' ability to control the host immune responses (7,11).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Parenteral vaccines are available for reduction of clinical signs owing to CIVs, including individual H3N8 or H3N2 vaccines and combination (bivalent) vaccines. 82,83 No commercially available vaccines are available for reduction of clinical signs caused by CRCoV and CHV.…”
Section: Prevention Of Canine Infectious Respiratory Diseasementioning
confidence: 99%